2016
DOI: 10.1111/nmo.12904
|View full text |Cite
|
Sign up to set email alerts
|

GABA‐producing Bifidobacterium dentium modulates visceral sensitivity in the intestine

Abstract: BackgroundRecurrent abdominal pain is a common and costly health‐care problem attributed, in part, to visceral hypersensitivity. Increasing evidence suggests that gut bacteria contribute to abdominal pain perception by modulating the microbiome‐gut‐brain axis. However, specific microbial signals remain poorly defined. γ‐aminobutyric acid (GABA) is a principal inhibitory neurotransmitter and a key regulator of abdominal and central pain perception from peripheral afferent neurons. Although gut bacteria are repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
185
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(190 citation statements)
references
References 81 publications
2
185
1
2
Order By: Relevance
“…Recently, one Lactobacillus strain and four strains of Bifidobacterium isolated from the human intestine have been reported to being able to produce GABA (Barrett et al, 2012). Furthermore, a very recent analysis on metagenomic data from the Human Microbiome Project suggests that genes encoding GAD could be present in a significant proportion of human gut microbiota (Pokusaeva et al, 2016). Lactobacilli include the strains with the highest GABA production, although this metabolic ability is more likely strain- rather than genus-related (Li and Cao, 2010).…”
Section: Bacterial Production Of Neuroactive Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, one Lactobacillus strain and four strains of Bifidobacterium isolated from the human intestine have been reported to being able to produce GABA (Barrett et al, 2012). Furthermore, a very recent analysis on metagenomic data from the Human Microbiome Project suggests that genes encoding GAD could be present in a significant proportion of human gut microbiota (Pokusaeva et al, 2016). Lactobacilli include the strains with the highest GABA production, although this metabolic ability is more likely strain- rather than genus-related (Li and Cao, 2010).…”
Section: Bacterial Production Of Neuroactive Moleculesmentioning
confidence: 99%
“…As far as we know, only one study concerning the modulation of host Glutamate/GABAergic systems by GABA/Glu producing gut-colonizing bacteria is available in the literature (Bravo et al, 2011). A recent study has demonstrated that a GABA-producing Bifidobacterium dentium is able to attenuate sensitivity of dorsal root ganglia neurons in a rat model of visceral pain (Pokusaeva et al, 2016). It is worth noting that these few examples refer to the limited number of studies on interaction between gut microbiota and the host nervous system which is currently available.…”
Section: Glu/gaba: Receptors Signaling and Transportmentioning
confidence: 99%
“…and Bifidobacterium spp. improves the protein synthesis, concentration of growth hormones in the brain and regulate the lipid levels in serum [56]. Another neuroactive molecule produced by Escherichia spp.…”
Section: Neurotransmittersmentioning
confidence: 99%
“…Moreover, both prokaryotes and eukaryotes synthesize γ-aminobutyric acid (GABA), a major inhibitory neurotransmitter of the CNS, through the decarboxylation of Glu by glutamate decarboxylase (GAD) and genes encoding GAD are present in the gut microbiota (Lactobacillus, Bifidobacterium) than can synthesize GABA from Glu in the distal intestinal lumen. Commensal Bifidobacterium dentium produce GABA via enzymatic decarboxylation of glutamate by GadB and daily oral administration of this specific Bifidobacterium strain induced the production of GABA [21].…”
Section: Origin Of Dietary Glu In the Gutmentioning
confidence: 99%